Accessibility Analysis for Healthcare Centers using Gravity Model and Geospatial Techniques - Raju, Shanmathi Rekha; Wajid, Shayesta; Radhakrishnan, Nisha; Mathew, Samson (TeMA - Journal of Land Use, Mobility and Environment, 2020)
India’s healthcare facilities continue to be limited and the current number of hospitals is not sufficient to meet the demands of the increasing population. In this study the multi-specialty hospitals handling sudden trauma such as cardiac arrests, strokes, burns, accidents, and major illnesses that were considered and analyzed for the ease of access within the city. The spatial accessibility index is measured using the Modified Three-step Floating Catchment Area which incorporates emergency factors in addition to travel time in travel impedance function. The findings shows that all hospitals are currently found to be collectively located near to the city center and wards located in the periphery of the city having very low spatial access to healthcare facilities. The index also aids in delineating the healthcare deprived areas and over-served areas within the city. This identification is essential for the future planning of new healthcare services, to improve the capacity and ease of access to the existing healthcare facilities. The model of this investigative study can be extended further to all cities to assist in the pre-planning for provision of adequate healthcare facilities. Such information will be advantageous, to public health officials and policy/decision makers involved in urban expansion planning, for ensuring better and quicker access to health services with minimum delay in the event of emergencies.